2021
DOI: 10.1016/j.jtho.2021.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pathologic Response in Lymph Nodes of Patients With Lung Cancer Receiving Neoadjuvant Chemotherapy

Abstract: Introduction: Major pathologic response (MPR), defined as residual viable tumor of less than or equal to 10%, currently serves as a surrogate end point for survival for patients with resectable NSCLC after neoadjuvant chemotherapy. However, the significance of pathologic response in lymph nodes harboring metastatic tumors in such patients remains uncertain. Therefore, we studied the effect of neoadjuvant chemotherapy on resected positive lymph nodes and determined if the degree of pathologic response in the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The evaluation of primary tumor response was performed as previously described: % of residual tumor = viable tumor area/total tumor bed area, whereby the total tumor bed = residual viable tumors + regression bed + necrosis. 30 , 31 …”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of primary tumor response was performed as previously described: % of residual tumor = viable tumor area/total tumor bed area, whereby the total tumor bed = residual viable tumors + regression bed + necrosis. 30 , 31 …”
Section: Methodsmentioning
confidence: 99%
“…PR has also been evaluated in metastatic lymph nodes resected after neoadjuvant chemotherapy, and studies have shown that patients with MPR-positive lymph nodes have a better survival than those with MPR-negative lymph nodes; however, there is still no consensus on cut-offs to define MPR in lymph nodes [ 33 , 34 ]. Of note, Pater et al [ 33 ] showed that, among patients with resectable NSCLC treated with neoadjuvant chemotherapy that did not achieve MPR in primary tumors, patients with MPR-positive lymph nodes, defined as a percentage of the viable tumor <70%, have better outcomes than patients with MPR-negative lymph nodes, suggesting that this information may help to better stratify patients for prognosis. Nevertheless, the clinical impact of evaluating MPR in lymph nodes, as well as its diagnostic reproducibility among pathologists, is still under investigation [ 28 ].…”
Section: Pathological Responsementioning
confidence: 99%
“…MPR is predictive of long-term survival benefit in neoadjuvant chemotherapy-treated patients with NSCLC [ 22 25 ] and has been implemented as candidate surrogate endpoint for evaluating novel chemotherapies and immunotherapy response, given the rare frequency of pCR following neoadjuvant chemotherapy in NSCLC (median 4%) [ 2 ].…”
Section: Non-small-cell Lung Cancermentioning
confidence: 99%